Polymer nanocomposites handbook - Gupta, Rakesh K. (Rakesh Kumar), 1954-; Kennel, Elliot; Kim, Kwang-Jea, 1962- (Boca Raton, FL : CRC Press, 2010)
Reflecting the exceptional growth in the use of nanostructured materials for an increasing range of industrial applications, Polymer Nanocomposites Handbook comprehensively covers the synthesis of nanomaterials that act as the building blocks of polymer nanocomposites and polymers that act as matrix materials. From early history to new technologies, the book guides readers through the development of nanocomposites and their broad and rapidly developing applications from flame retardant properties to advances in polymer compounding. Using examples from today$1 (Bs leading academic and industrial research labs, top scientists provide in-depth discussions of the science, processing, and technology that have accompanied nanocomposites$1 (Bascension into the world of chemical and materials science. With nineteen chapters authored by world leaders in nanocomposite research, this handbook provides diverse and authoritative coverage on the scientific underpinnings and revolutionary discoveries related to this promising field.s
Corral, M. Shofner, and D. Simeon -- Polymer Nanocomposites Containing Vapor-Grown Carbon Fibers Aligned by Magnetic or Electric Field Processing, T. Takahashi and K. Yonetake -- Utility of Carbonaceous Nanofillers in Elastomers and Thermoplastic Elastomeric Gels, J.K. Kim, M. Pagalicawan, and V. Sridhar -- Nanocomposites of Liquid Crystalline Polymers Dispersed in Polyester Matrices, C.H. Song and A.I. Isayev -- Transmission Electron Microscopy and Related Techniques in the Structure Characterization of Polymer Nanocomposites, V.K. Berry -- Mechanical Properties of Clay-Containing Polymeric Nanocomposites, L.A. Utracki -- Appendices, Mass Transport through Polymer Nanocomposites, D. De Kee and K.J. Frederic -- Flammability Properties of Polymer Nanocomposites, J. Zhu and C.A. Wilkie -- Electrical Properties of Nanoparticle-Filled Polymers, E.B. Kennel -- Thermal Conductivity of Polymer Nanocomposites, S. Agarwal and R.K. Gupta -- Bio-Based Nanocomposites from Functionalized Plant Oils, C.-K. Hong, J. Lu, and R.P. Wool.
Corral, M. Shofner, and D. Simeon -- Polymer Nanocomposites Containing Vapor-Grown Carbon Fibers Aligned by Magnetic or Electric Field Processing, T. Takahashi and K. Yonetake -- Utility of Carbonaceous Nanofillers in Elastomers and Thermoplastic Elastomeric Gels, J.K. Kim, M. Pagalicawan, and V. Sridhar -- Nanocomposites of Liquid Crystalline Polymers Dispersed in Polyester Matrices, C.H. Song and A.I. Isayev -- Transmission Electron Microscopy and Related Techniques in the Structure Characterization of Polymer Nanocomposites, V.K. Berry -- Mechanical Properties of Clay-Containing Polymeric Nanocomposites, L.A. Utracki -- Appendices, Mass Transport through Polymer Nanocomposites, D. De Kee and K.J. Frederic -- Flammability Properties of Polymer Nanocomposites, J. Zhu and C.A. Wilkie -- Electrical Properties of Nanoparticle-Filled Polymers, E.B. Kennel -- Thermal Conductivity of Polymer Nanocomposites, S. Agarwal and R.K. Gupta -- Bio-Based Nanocomposites from Functionalized Plant Oils, C.-K. Hong, J. Lu, and R.P. Wool.
Includes bibliographical references (p. 532) and index.
1
Keywords: Polymeric composites -- Handbooks, manuals, etc; Nanostructured materials -- Handbooks, manuals, etc; Polymer nanocomposites; Polyester matrices; Nanoparticles; Nanocomposites (Materials)